2003
DOI: 10.1021/jo030029w
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Translocation by Modified Phorbol Esters with Functionalized Lipophilic Regions

Abstract: Several novel phorbol esters were prepared with polar functional groups terminating their C12 and/or C13 acyl chains. Designed to be inhibitory protein kinase C (PKC) ligands, these phorbol analogues contain various polar functional groups (amide, ester, carboxylic acid, or quaternary ammonium salt) to prevent membrane insertion of the PKC-phorbol ester complex. All phorbol derivatives were synthesized with use of diterpene starting materials obtained from croton oil, the seed oil of Croton tiglium. The abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…The overall result, therefore, could be partial agonism at the level of the in vivo PKCs. The plausibility of this partial association with membranes was previously shown (51). In addition, Wada et al reported (29) that a phorbol ester with a hydrophilic 12-ester chain could inhibit the activation of PKC-␣ by PMA.…”
Section: Discussionmentioning
confidence: 68%
“…The overall result, therefore, could be partial agonism at the level of the in vivo PKCs. The plausibility of this partial association with membranes was previously shown (51). In addition, Wada et al reported (29) that a phorbol ester with a hydrophilic 12-ester chain could inhibit the activation of PKC-␣ by PMA.…”
Section: Discussionmentioning
confidence: 68%
“…a, TSLP was indeed induced in all settings. Croton oil, which contains phorbol esters, was particularly potent, but shaving, SDS and tape stripping were also effective. The induction of TSLP mRNA was rapid, but still detectable after 18 h. Intriguingly, this mild irritation affecting approximately 20% of the murine skin area was sufficient to initiate a systemic TSLP response.…”
Section: Resultsmentioning
confidence: 99%
“…Such phorbol ester lipophilic domain is thought to be responsible for redistributing a phorbolprotein complex to the plasma membrane. 174 Biotransformation of phorbol esters by intestinal bacteria has been successfully achieved. 175 …”
Section: Tumor Promotionmentioning
confidence: 99%